Rural Extension and the School: conversations on the making of Life Projects in the Countryside - Dionéia Maria Samua Vieira; Luci Teresinha Marchiori dos Santos Bernardi; Luis Pedro Hillesheim (Universidade Federal do Norte do Tocantins, 2022)
The paper presents a reflection on the relationship between Rural Extension and Formative Practices in Schools developed during the dialogical process with the community and through a curriculum component of the diverse area, aiming to think about the making of Life Projects of rural youths. Using a bibliographical methodology, it revisits the timeline and the concepts of Agricultural Extension, weaving a dialogue between the objectives and aims of this service in the current scenario, putting into perspective the relationship established with the school. It presents a formative experience proposed in the Elementary School Curriculum in a school in Rio Grande do Sul, Brazil, from 2002 onwards, through a subject called Local Development, which represents a community move to stimulate the permanence in the countryside and to strengthen the development of agricultural activities. It highlights the importance of an educational practice founded on the dialogue and on interdisciplinary work, anchored the in the possible relationships to be stablished between Agricultural Extension and the school. It also verifies that such educational opportunities mobilize the Life Project, giving meaning to the young population of the countryside, to its own development and to its location.